THEORETICAL AND APPLIED ANALYSIS OF CULTURAL POLICY IN RESEARCH OF DOMESTIC AND FOREIGN SCIENTISTS - Kinash , I.P.; Senychak , V.V. (The actual problems of regional economy development, 2016)
The article analyses the cultural policies in research of domestic and foreign scientists. It was found that around the world it is a part of social policy and an important tool for development. The role of culture as a powerful means of consolidation of society, strengthening of national identity and patriotism is being determined. Implementation of cultural policy of Ukraine through the idea of national cultural revival and restoration of the unity of the state has been suggested. JEL: Z 10